Comparative Evaluation of the Effect of Manufacturing Process on Distortion of Rotary ProFile and Twisted File: An in Vitro SEM Study - Swati Sharma; Rajendra Kumar Tewari; Surendra Kumar Mishra; Pankaj Kharade (Journal of Dental Research, Dental Clinics, Dental Prospects, 2015)
Background and aims. The manufacturing process of rotary Ni-Ti file can influence its resistance to fracture. The rotary ProFile (Dentsply-Maillefer, Baillagues, Switzerland) is manufactured by grinding mechanism whereas Twisted File (Sybron Endo, USA) is manufactured with a twisting method. The purpose of this study was to comparatively evaluate the effect of manufacturing process on distortion of rotary ProFile and Twisted files using scanning electron microscopy after in vitro use. Materials and methods. Five sets of each type of file were used for this study -rotary ProFile (group A) and Twisted file (group B). Each set was used according to manufacturer’s instructions to prepare 5 mesial canals of extracted mandibular molars. The changes in files were observed under a scanning electron microscope at ×18, ×100, ×250 and ×500 magnifications. Observations were classified as intact with no discernible distortion, intact but with unwinding, and fractured. Group A and B were then compared for deformation and fracture using two-proportion z-test. Results. On SEM observation, used rotary ProFile showed microfractures along the machining grooves whereas Twisted file showed crack propagation that was perpendicular to the machining marks. On statistical analysis, no significant difference was found between ProFile and Twisted file for deformation (P=0.642) and fracture (P=0.475). Conclusion. Within the experimental protocol of this study, it was concluded that both ProFile and Twisted files exhibited visible sign of distortion before fracture. But Twisted file gained edge over ProFile because of its manufacture design and unparalleled resistance to breakage.